Le Fayoum : archéologie, histoire, religion : actes du sixième colloque international, Montpellier, 26-28 octobre 2016 - Chaufray, Marie-Pierre, 1980-; Guermeur, Ivan; Lippert, Sandra Luisa; Rondot, Vincent (Harrassowitz Verlag, 2018)
The Sixth International Conference on the Fayum, which took place in October 2016 at Montpellier, reunited Egyptologists, archaeologists, papyrologists and Coptologists whose research concerns divers aspects of life in the Fayum oasis in Antiquity. The volume contains 13 articles in English, French and German on the colonization, administration, judiciary, business life, scribal education, religion and religious communities, specificities of the regional onomastic, distinctive dialectal features etc. The time frame covers nearly 3000 years, from the the Middle Kingdom to the Coptic/Early Arab period (2nd mil. BCE to 9th c. CE), with a focus on the region?s florescence during the Graeco-Roman Period (332 BCE?4th c. CE).